Regional infrastructure policy and its impact on productivity: a comparison of Germany and France - Andreas Stephan (Wissenschaftszentrum Berlin für Sozialforschung (WZB), 2001)
This paper describes the different institutional frameworks for infrastructure policy in Germany and France. The economic effects of infrastructure are estimated econometrically for German and French regions. We find evidence that regional road infrastructure has a significant impact on regional output. Moreover, we find evidence that for Germany the priority of promoting equal living conditions throughout the regions is an important determinant of regional infrastructure policy. – – Die Arbeit beschreibt die unterschiedlichen institutionellen Rahmenbedingungen, unter welchen Planung und Finanzierung von Infrastruktur in Deutschland und Frankreich realisiert werden. Weiterhin werden die wirtschaftlichen Effekte von Infrastruktur ökonometrisch für deutsche und französische Regionen geschätzt. Es wird Evidenz dafür gefunden, dass regionale Straßeninfrastruktur einen signifikanten Einfluss auf den regionalen Output hat. Wir finden auch empirische Evidenz dafür, dass in Deutschland die Priorität für die Angleichung der Lebensverhältnisse in den Regionen eine wichtige Determinante für regionale Infrastrukturpolitik ist.
Keywords: C33; H54; O57; 330; Infrastructure Policy; Productivity; Germany; France